Pelatihan Mesin Cnc Laser Dalam Meningkatkan Jiwa Wirausaha Bagi Generasi Muda - Eriansyah Saputra Hasibuan; Nurmahendra Harahap; Mutiara Widasari Sitopu; Indah Vusvita Sari (STMIK Royal, 2022)
Abstract: In today's increasingly advanced era, but with limited funds, it requires the community to carry out various innovations that can develop an entrepreneurial spirit in order to improve the economy. In the implementation of service activities carried out for 2 days. Where the first day contains an explanation of the use of CNC machines and the basics of CNC implementation, while on the second day the process of printing the artwork that has been designed by the previous participants is carried out directly, because the printing process takes a long time ranging from 4 to 5 hours in printing one design. , depending on the level of difficulty of the design you want to print. The activity was carried out from 9-10 December 2021 at the Aviation Vocational School with a total of 40 students. By holding this service, it is hoped that students will grow an entrepreneurial spirit, so they are able to do entrepreneurship, especially in the field of acrylic art. With the dedication that has been carried out, enthusiastically the young generation in this case the aviation vocational school students can open entrepreneurs in the field of carving by utilizing acrylic and CNC machines which have economic value among society in general and young people in particular so as to improve the family economy. Keywords: entrepreneur; innovation; acrylic Abstrak: Pada zaman yang semakin maju saat ini, namun dengan keterbatasan dana, menuntut masyarakat untuk melakukan berbagai inovasi yang dapat mengembangkan jiwa wirasusaha guna meningkatkan ekonomi. Dalam pelaksanaan kegiatan pengabdian dilakukan selama 2 hari. Dimana hari pertama berisi tentang penjelasan penggunaan mesin CNC dan dasar-dasar penerapan CNC sedangkan pada hari kedua dilakukan langsung proses pencetakan karya seni yang telah di desain oleh peserta sebelumnya, dikarenakan proses pencetakan dibutuhkan waktu yang cukup lama berkisar 4 sampai 5 jam dalam pencetakkan satu desain, tergantung tingkat kesulitan desain yang ingin dicetak. Kegiatan dilakukan mulai tanggal 9-10 Desember 2021 di sekolah SMK Penerbangan dengan jumlah peserta 40 siswa. Dengan diadakan pengabdian ini diharapakan kepada siswa untuk menumbuhkan jiwa kewirausahaan, sehingga mampu melakukan wirausaha khususnya dibidang seni akrilik. Dengan adanya pengabdian yang telah dilakukan, membuat antusias generasi muda dalam hal ini siswa SMK penerbangan dapat membuka wirausaha dibidang seni ukir dengan memanfaatkan akrilik dan mesin CNC yang memiliki nilai ekonomis dikalangan masyarakat pada umumnya dan kalangan muda pada khususnya sehingga dapat meningkatkan ekonomi keluarga. Kata kunci: wirusaha; inovasi; akrilik